2014
DOI: 10.1177/1010539514560057
|View full text |Cite
|
Sign up to set email alerts
|

Direct Economic Burden and Influencing Factors in Patients With Hepatitis B Virus Related Diseases in Jiangsu, China

Abstract: The purpose of this study was to explore direct economic burden and its influencing factors in patients with hepatitis B virus (HBV) related diseases. Time phasing continuous sampling was used to select patients from August 1, 2012, to December 31, 2012, in 3 county hospitals of 3 model regions in Jiangsu Province, China. A total of 436 outpatients and 196 inpatients were observed. The average direct economic burden of HBV-associated admission was US$107.11 for outpatients, and drug fees accounted for 74%; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…However, in 2020, hepatitis imposed a heavy economic burden on HBV sufferers, their families and the society [ 26 ]. In Shandong province, Lu et al estimated the inpatient medical costs of hepatitis B-related diseases ranged from $US2954 to $US10,635 per patient and Zhang et al found that in Jiangsu province the direct economic costs of HBV-related diseases ranged from $US107 for outpatients to $US3193 for inpatients [ 27 , 28 ]. These prevalence rates and public health costs call for expanded vaccinations of susceptible adults and the need for public health officials to intervene to reduce hepatitis B infections in adults.…”
Section: Introductionmentioning
confidence: 99%
“…However, in 2020, hepatitis imposed a heavy economic burden on HBV sufferers, their families and the society [ 26 ]. In Shandong province, Lu et al estimated the inpatient medical costs of hepatitis B-related diseases ranged from $US2954 to $US10,635 per patient and Zhang et al found that in Jiangsu province the direct economic costs of HBV-related diseases ranged from $US107 for outpatients to $US3193 for inpatients [ 27 , 28 ]. These prevalence rates and public health costs call for expanded vaccinations of susceptible adults and the need for public health officials to intervene to reduce hepatitis B infections in adults.…”
Section: Introductionmentioning
confidence: 99%
“…In Shandong province, Lu et al estimated the in-patient costs of hepatitis B-related diseases ranged from $US2954 to $US10635 per patient, 5 and Zhang et al found that in Jiangsu province the direct economic costs of HBV-related diseases ranged from $US107 for out-patients to $US3193 for in-patients. 6 All these studies advocated the need for public health officials to intervene to reduce HBV-related diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Annual cost of LVD (GlaxoSmithKline Ltd.) was US $865.39,ETV(Shanghai Squibb Company) was US $2006.57.Annual direct medical costs for managing these CHB-related disease states were derived from our previous study[30]. CHB: $4257.84, CC: $3910.69, DC: $6434.70, HCC: $4874.21.…”
Section: Methodsmentioning
confidence: 99%